Lipid profile in menopausal women of two ethnic groups - N. V. Semenova; I. M. Madaeva; M. A. Darenskaya; O. A. Gavrilova; R. M. Zhambalova; L. I. Kolesnikova (Acta Biomedica Scientifica)
Background. The hormonal alteration in menopause can lead to changes in the lipid metabolism parameters. The results of studies on this issue are ambiguous and suggest ethno-specific changes in the lipid profile. Aim: comparative assessment of lipid metabolism parameters in women of Caucasian and Asian races in peri- and postmenopause. Materials and methods. 146 women of Caucasian (ethnic group - Russian (n = 82)) and Asian (ethnic group - Buryats (n = 64)) races participated as volunteers in the prospective non-randomized study for the period 2012-2016. Each ethnic group was divided into three subgroups - women of reproductive age, women in perimenopause, and in postmenopause, according to the gynecological status. The lipid metabolism parameters were determined by the enzymatic method on a biochemical analyzer BTS-330. When analyzing the intergroup differences for independent samples, nonparametric criteria were used. Results. In Russian perimenopausal women, compared with women of reproductive age, we registered an increase in triglycerol levels by 1.90 times (p < 0.05) and cholesterol of very low density lipoproteins by 2.10 times (p < 0.05), followed by an increase of total cholesterol levels by 1.22 times (p < 0.05) and low-density lipoprotein cholesterol by 1.40 times (p < 0.05) in postmenopausal period. In representatives of the Buryat ethnos, the changes in the lipid metabolism parameters were detected only in postmenopause, they consisted in increased total cholesterol levels - by 1.31 times (p < 0.05) and low density lipoprotein cholesterol - by 1.45 times (p < 0.05). Conclusions. Changes in the lipid profile in menopause are more pronounced in representatives of the Russian ethnic group.